Lung xenogenic injury: does anticoagulation help?. (5th February 2013) - Azimzadeh, Agnes; Burdorf, Lars; Rybak, Elana; Riner, Andrea; Zhang, Tianshu; Broos, Katleen; Braileanu, Gheorghe; Rodriguez, Rachael; Cheng, Xiangfei; Deckmyn, Hans; Phelps, Carol; Ayares, David; et al.
Abstract : The shortage of human organ donors remains a major limitation to the field of transplantation [1], and can potentially be solved using xenografts. During the past decade, many advances have been made to address the major initial immunological obstacle to "discordant" pig‐to‐human solid organ transplantation: hyperacute rejection (HAR). As organs from unmodified pigs were evaluated in animal models, HAR was found to be primarily a consequence of the recipient's preformed anti‐pig antibodies binding on porcine vascular endothelial cells leading to subsequent complement activation, thrombosis and graft failure [2]. This process occurs within minutes to hours of human blood perfusion in porcine organs. Since the carbohydrate structure Galactose‐α(1, 3‐Galactose (Gal) is recognized by over 80% of anti‐pig antibodies found in man, genetically modified galactosyl transferase knock‐out (GalTKO) pig organs have been developed [3, 4]. Endothelium and parenchymal cells from GalTKO animals lack the Galα1, 3Gal epitope. As predicted, heart and kidney transplant studies in baboons showed that the GalTKO phenotype is associated with decreased antibody binding, reduced activation of the complement cascade and prolonged graft survival [5–8]. However, delayed xenograft rejection, consumptive coagulopathy and microangiopathy limit long‐term outcomes. Xenogenic lungs are even more sensitive to xenogenic injury [9, 10], even with additional expression of complement regulatory protein human CD46 [Burdorf et al]. Immunohistology and biochemical evidence and work by others implicated inflammation and coagulation cascade activation as residual xenogenic injury pathways. To determine the role of these pathways in lung xenogenic injury, our group is evaluating new transgenic pigs [11] and various pharmacologic approaches. New transgenes include human thrombomodulin (hTM), endothelial protein C receptor (EPCR) and ectonucleoside triphosphate diphosphohydrolase‐1 (CD39). Pharmacologic interventions consist in targeting platelet receptors (GPIb, GPIIbIIIa), thrombin (hirulog) and adding exogenous activated protein C to perfused human blood and administering desmopressin to lung donor pigs. The differential effects of these interventions on lung physiological parameters, platelet and coagulation activation will be summarized. Future work will place emphasis on combined targeting of these pathways. Acknowledgments: Funded in part by NIH (IU19A1090959, 1U01AI066335) and by gifts from Revivicor and United Therapeutics. References 1. Cooper DKC. Xenografting: how great is the clinical need? Xeno 1993; 1: 25–26. 2. Pierson RNIII. Antibody‐mediated xenograft injury: mechanisms and protective strategies. Transpl Immunol 2009; 21: 65–69. 3. Phelps CJ, Koike C, Vaught TD et al.Production of alpha 1, 3‐galactosyltransferase‐deficient pigs. Science 2003; 299: 411–414. 4. Kolber‐ Simonds D, Lail L, Watt SR et al. Production of alpha‐1, 3‐galactosyltransferase null pigs by means of nuclear transfer with fibroblasts bearing loss of heterozygosity mutations. Proc Natl Acad Sci U S A 2004; 101: 7335–7340. 5. Tseng YL, Kuwaki K, Dor FJ et al. alpha1, 3‐Galactosyltransferase gene‐knockout pig heart transplantation in baboons with survival approaching 6 months. Transplantation 2005; 80: 1493–1500. 6. Kuwaki K, Tseng YL, Dor FJet al. Heart transplantation in baboons using alpha1, 3‐galactosyltransferase gene‐knockout pigs as donors: initial experience. Nat Med 2005; 11: 29–31. 7. Yamada K, Yazawa K, Shimizu Aet al. Marked prolongation of porcine renal xenograft survival in baboons through the use of alpha1, 3‐galactosyltransferase gene‐knockout donors and the cotransplantation of vascularized thymic tissue. Nat Med 2005; 11: 32–34. 8. Mohiuddin MM, Corcoran PC, Singh AK, et al. B‐cell depletion extends the survival of GTKO.hCD46Tg pig heart xenografts in baboons for up to 8 months. Am J Transplant. 2012; 12:763–71. 9. Nguyen BN, Azimzadeh AM, Zhang T, et al. Life‐supporting function of genetically modified swine lungs in baboons. J Thorac Cardiovasc Surg 2007; 133: 1354–1363. 10. Nguyen BN, Azimzadeh AM, Schroeder C et al. Absence of Gal epitope prolongs survival of swine lungs in an ex vivo model of hyperacute rejection. Xenotransplantation. 2011; 18:94–107. 11. Cooper DK, Ekser B, Burlak C et al. Clinical lung xenotransplantation – what donor genetic modifications may be necessary? Xenotransplantation. 2012; 19:144–58.